2013
DOI: 10.1126/science.1230381
|View full text |Cite
|
Sign up to set email alerts
|

Supercomplex Assembly Determines Electron Flux in the Mitochondrial Electron Transport Chain

Abstract: The textbook description of mitochondrial respiratory complexes (RCs) views them as free-moving entities linked by the mobile carriers coenzyme Q (CoQ) and cytochrome c (cyt c). This model (known as the fluid model) is challenged by the proposal that all RCs except complex II can associate in supercomplexes (SCs). The proposed SCs are the respirasome (complexes I, III, and IV), complexes I and III, and complexes III and IV. The role of SCs is unclear, and their existence is debated. By genetic modulation of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
760
11
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 723 publications
(833 citation statements)
references
References 26 publications
52
760
11
10
Order By: Relevance
“…We did not observe SC I+III2+IV probably because the mitochondria were purified from C57B6 mice that are deficient for Cox7a2l (Cyt c oxidase subunit VIIa polypeptide 2 like) and therefore cannot have III+IV association (Supplementary Figure 6e). 28 GB induced a significant loss in monomeric complex I and III activities, as shown previously (Figures 6c and f). In D-solubilized samples, complex I and III activities of SC I+III 2 were not significantly changed by GB, even though much more SC was formed after GB treatment, indicating that the specific activity of these complexes was reduced by GB treatment.…”
Section: Gb-induced Ros Requires a Functional Respiratory Chainsupporting
confidence: 89%
See 2 more Smart Citations
“…We did not observe SC I+III2+IV probably because the mitochondria were purified from C57B6 mice that are deficient for Cox7a2l (Cyt c oxidase subunit VIIa polypeptide 2 like) and therefore cannot have III+IV association (Supplementary Figure 6e). 28 GB induced a significant loss in monomeric complex I and III activities, as shown previously (Figures 6c and f). In D-solubilized samples, complex I and III activities of SC I+III 2 were not significantly changed by GB, even though much more SC was formed after GB treatment, indicating that the specific activity of these complexes was reduced by GB treatment.…”
Section: Gb-induced Ros Requires a Functional Respiratory Chainsupporting
confidence: 89%
“…In the presence of cycloheximide that inhibits protein synthesis and de novo complex I production, GB and P still cleave complex I subunits, indicating that GB is acting on fully assembled complex I (Supplementary Figure 2d). [28][29][30] NDUFS3 and NDUFA9 complex I subunits not cleaved by GB were still present long after the cells had died following 4 h of GB treatment (Supplementary Figure 2e). Altogether, GB, independently of caspases, cleaves NDUFV1, NDUFS2 and NDUFS1 in cells undergoing killer cell attack.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flux experiments have shown that the formation of the respirasome allows for substrate channelling by decreasing the distance in which electrons travel between mobile electron carriers and the OXPHOS complexes. This finding is supported by in-gel enzymatic assays that demonstrate respirasome catalytic activity in a range of eukaryotes [16,24,25]. In addition, the formation of the respirasome has also been proposed to limit oxidative stress [26].…”
Section: Oxphos Supercomplexesmentioning
confidence: 78%
“…1 It has antioxidant properties, regulates both transition pore and uncoupling proteins, and it is an obligated substrate for both β-oxidation of fatty acids and pyrimidine nucleotide biosynthesis. 2 CoQ 10 deficiency impairs oxidative phosphorylation and causes clinically heterogeneous mitochondrial diseases, 3 including an encephalomyopathy form with muscle disorders and myoglobinuria; an ataxic form with atrophic cerebellum; a severe infantile form with renal failure; an isolated myopathy, and nephrotic syndrome, have been so far described.…”
Section: Introductionmentioning
confidence: 99%